Diversity of mosquitoes (Diptera: Culicidae) in yellow fever risk areas in the Upper Paraná Atlantic Forest of Misiones, Argentina - Brividoro, Melina Victoria (2023)
Mosquitoes (Diptera, Culicidae) are a very diverse taxonomic group, which mainly inhabits tropical-subtropical zones, with many species of public health significance considered vectors of different pathogens, such as the yellow fever virus (YFV) (Flavivirus, Flaviviridae). Our aim is to know the diversity of mosquito species in the Upper Paraná Atlantic Forest and determine the presence of vector of YFV. The study was carried out in April and November 2021 in three Provincial Parks: Piñalito, Cruce Caballero and Moconá. We used CDC-light traps and net/manual aspirator as collection techniques. Overall, across the three sites we collected 536 female adult mosquitoes and identified 13 genera and 33 species. Considering all study sites, we obtained a high Margalef diversity index (DMG=5.8). Considering all study sites together, the species with the highest relative abundance (RA) were Haemagogus leucocelaenus (Dyar and Shannon) (RA=15.3%, N=37) and Psorophora ferox (von Humboldt) (RA=16.1%, N=39). In relation to species involved in the sylvatic YF cycle, we collected Hg. leucocelaenus (a main vectors) in the three study areas and nine other species considered potential vectors (7 species in Piñalito, 5 in Cruce Caballero and 2 in Moconá). Although all of the species we found have been previously reported in Misiones, none had been documented in the studied areas; so, we expanded the distribution of all of them. We found a high diversity of species reported for Misiones (33 of 194 species), which could be related to the variety of habitats present in this portion of the Upper Paraná Atlantic Forest. In addition, many of these species are of sanitary importance, which makes these areas of special interest for developing plans to monitor insects and their associated viruses.